MARVA: Modular Architecture for Robust Visual Agents - Schenkel, Vanessa; Ramos, Gabriel de Oliveira (Anais da Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região Sul (ERAMIA-RS); 2025: Anais da I Escola Regional de Aprendizado de Máquina e Inteligência Artificial da Região SulDO - 10.5753/eramiars.2025.16789, 2025)
Generalization in visual RL is challenging: small visual shifts can degrade performance. We present MARVA, a dual-regularization extension of MaDi combining a GRL-based discriminator and a contrastive (InfoNCE) loss on masked views. On walker-walk, MARVA matches baseline performance in easier domains and improves robustness in video_hard and DistractingCS.